Home bias no mercado de capitais brasileiro: um estudo sobre a custódia de investidores em ações - Lersch, Maurício Silveira (2015)
This paper presents an analysis of the concentration of the portfolio of Brazilian in-vestors in shares of companies that they work in order to observe whether the Home Bias applied to the sample. Our study was conducted with a sample taken custody of 86 clients of a broker of securities, which are actual data market. We restrict the se-lection of the sample for the half of the sample be of clients who work in open capital companies and the other half, not. It analyzed by a cross section the allocation shares of the investors in the companies they work for and found what percentage of this is holding in their portfolios, compared to a sample of investors who do not work in the company. In addition to these analyzes, we separate the sample by the total value of the portfolio and carried out the same studies with the set different groups of the sample. As a robustness analysis, we identify listed companies that do not adopt the remuneration with shares as a sub sample of the study. As a result, we find evidence that employees has investing significantly more (or in portfolio or in values) in shares of the companies where they work, showing a familiarity bias in making investment decisions.